Гностические мотивы в творчестве Владимира Набокова (на примере повести Соглядатай) - Kortus, Nadzieja (Studia Rossica Posnaniensia, 2019)
There are many works that discuss the prose of Vladimir Nabokov in the Gnostic context. The article is an attempt to confront the short novel The Eye of this outstanding writer with the most important determinants of the Gnostic initiation.